Martin Luther King, Jr. : young man with a dream - Millender, Dharathula H.; Fiorentino, Al (New York : Aladdin Books ; London : Collier Macmillan Publishers, 1986)
A biography, emphasizing the early years, of the civil rights leader whose philosophy and practice of nonviolent civil disobedience helped American blacks win many battles for equal rights.
Reprint. Originally published: Indianapolis : Bobbs-Merill, 1969. (Childhood of famous Americans series)
Keywords: King, Martin Luther, -- Jr., -- 1929-1968 -- Childhood and youth -- Juvenile literature; King, Martin Luther, -- Jr., -- 1929-1968 -- Childhood and youth; African Americans -- Biography -- Juvenile literature; Baptists -- United States -- Clergy -- Biography -- Juvenile literature; African Americans -- Civil rights -- Juvenile literature; Clergy; Civil rights workers; African Americans -- Biography